Federal Tax Funding to "Assist" State Tobacco Control Lobbying (Tufts Archival Research Center, 2007)
Article arguing that federal taxes are funding state tobacco control lobbying. Argues this is happening through National Cancer Institute (NCI) ASSIST program, as the government gives money to NCS and then NCI funds anti-tobacco advocates. Questions whether ASSIST shows contempt for Congress and what taxpayers dollars buy with ASSIST funds. Wonders if policy intervention is the proper mission of the NCI. Describes ASSIST.